Impacts of parental health on children's development of personality traits and problem behavior: Evidence from parental health shocks - Brant Morefield; Andrea M. Mühlenweg; Franz Westermaier (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2011)
In this paper, we examine how parental health affects children's development of personality traits and problem behavior. Based on a German mother-and-child data base, we draw on observed parental health shocks as a more exogenous source of health variation to identify these effects and control for child and family characteristics including variables reflecting initial endowments observed at birth. At the age of six, we observe that maternal health shocks in early childhood have significant impacts on children's emotional symptoms, hyperactivity and neuroticism. Paternal health seems to be less relevant for the development of these non-cognitive characteristics. However, we observe that paternal health shocks cause children to be more extraverted.
Keywords: I00; J24; I10; 330; Human capital; health; personality traits; non-cognitive skills; Kinder; Persönlichkeitspsychologie; Eltern; Gesundheit; Schock; Schätzung; Deutschland